Alternative method’s results for the non targeted determination of xenobiotics in food by means of high resolution and accuracy mass spectrometry - Rossana Scarpone (BMC, 2021)
Abstract The application of a high resolution and accurate mass spectrometry (HRAMS) approach to detect xenobiotics in different food matrices by means of non targeted determination by UHPLC-Orbitrap followed by data processing analysis was described. Three case studies were reported to demonstrate the possibility to identify unexpected substances in different food commodities overcomes targeted method. This innovative approach could lay the foundation for its applicability to routine analysis in the near future giving the possibility to open new horizons to the research of a wide range of xenobiotics.